1995
DOI: 10.1002/hup.470100207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking abstinence and nicotine abstinence on heart rate, activity and cigarette craving under field conditions

Abstract: In a field study heart rate, activity, cigarette consumption, craving for cigarettes, saliva cotinine and subjective ratings were assessed in 12 female subjects, smoking medium tadmedium nicotine cigarettes (TN). The habituated cigarettes were compared with a nearly nicotine-free/medium tar (0.08 mgl9.3 mg) cigarette (Tn) and with abstinence. Two recording periods of 3 days each were conducted in two consecutive weeks. Heart rate was highest with the TN cigarettes, 8 bpm lower on abstinence days and in between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…This would support recent findings that nicotine EC has a greater effect on abstinence and smoking reduction than placebo EC [24]. Additionally, studies with DNCs have reported effects on craving alleviation in abstaining smokers after one [25] and four [26] days of DNC use. This could be in part due to the potentially reinforcing chemicals still present in DNCs, or it may be because DNCs provide sensorimotor input more proximal to smoking than EC.…”
Section: Discussionsupporting
confidence: 88%
“…This would support recent findings that nicotine EC has a greater effect on abstinence and smoking reduction than placebo EC [24]. Additionally, studies with DNCs have reported effects on craving alleviation in abstaining smokers after one [25] and four [26] days of DNC use. This could be in part due to the potentially reinforcing chemicals still present in DNCs, or it may be because DNCs provide sensorimotor input more proximal to smoking than EC.…”
Section: Discussionsupporting
confidence: 88%
“…De-nicotinized cigarettes have also been found to reduce symptoms of nicotine withdrawal normally associated with tobacco abstinence (11,15,(17)(18)(19)(20)(21)(22)(23). It has been hypothesized that inhaling smoke with substantially reduced levels of nicotine may provide sensorimotor cues that moderate the craving for cigarettes and facilitate nicotine withdrawal (24).…”
Section: Introductionmentioning
confidence: 99%
“…Over 24 hours of abstinence, craving was significantly lower with DNCs than with no intervention [28] and this was also observed on some, though not all, measures of craving over 4 days of abstinence [36]. However, in a well-controlled study which hospitalised volunteers for 13 days, participants in the DNC and notreatment conditions did not differ in ratings of craving over 11 days of abstinence [38].…”
Section: De-nicotinised Cigarettesmentioning
confidence: 74%
“…The size of this effect is unknown, and regression analyses revealed significant individual differences, in that males and more dependent smokers reported more similar ratings between the two types of cigarette. A fair number of studies have however found similar craving suppression to nicotine containing cigarettes [7,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: De-nicotinised Cigarettesmentioning
confidence: 99%